THE EFFECT OF WORKING CAPITAL ON THE PROFIT OF PT UNILEVER INDONESIA TBK - Komar ekonomi bisnis; Yunita Eva Rizkiah (JEBS (Journal of Economic and Business Student), 2022)
This research has aimed to determined the effect of working capital on profitability in PT Unilever Indonesia Tbk. This research uses quantitative methods with simple regression analisis. The data collection technique is done by documenting samples taken from  PT Unilever Indonesia Tbk financial report data for the period 2015 -2019. The result showed that working capital has a strong relationship with ROA because it has value R= 0,791 and has an influence on  ROA of 62,6%, meanwhile 37,4% is influenced by other variables not examined. The problems that arise are : 1) competition with other companies at lower prices; 2) the company’s current liabilities are greater than the assets owned by the company so that it affects working capital in the company which result in negative working capital. The suggestions given are : 1) companies should be able to balance its working capital structure,2) pay more attention to the balance of current asset and current debt.